PENGARUH STORE ATMOSPHERE TERHADAP IMPULSE BUYING - supriono supriono (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
Fun atmosphere for consumers when doing shopping at the store is called Store Atmosphere (store atmosphere). Being very important because it is suspected to affect someone to make purchases that are sometimes unplanned (impulse buying). This research was conducted to test the influence of store atmosphere on impulse buying. Conducted in shopping center (retail) in Malang Indonesia. Includes quantitative research by taking data using questionnaire instruments and involving 116 respondents. The results showed that Store Atmosphere has a strong influence on consumers to do Impulse Buying.